A compact filtering antenna using dielectric strip resonator and parallel microstrip feed line. Issue 9 (18th June 2020) - Xu, Kai; Shi, Jin
Abstract: A filtering antenna using dielectric strip resonator and parallel microstrip feed line is proposed to achieve compact dielectric size and filtering response without gain reduction. The compact dielectric size is contributed by the dielectric strip resonator with high permittivity operated in the TMδ1 cavity mode, whose electric field distribution along the short side is far less than half‐wavelength distribution. Therefore, the size of the proposed dielectric strip resonator is smaller than the traditional dielectric patch resonator operated in the TM11 cavity mode. Additionally, the parallel placed microstrip line not only can excite the dielectric strip resonator for filtering response without gain reduction, but also can provide one upper‐edge radiation null for frequency selectivity enhancement. Compared with the reported filtering dielectric antennas, the proposed design exhibits the features of compact dielectric size, simple structure and wide stopband. For demonstration, one prototype operating at 4.9 GHz is fabricated, achieves the dielectric size of 0.00078 λ3 0 (λ0 is the wavelength in the free space at the center frequency), the measured peak gain of 7.1 dBi, the 10‐dB impedance matching bandwidth of 4%, the stopband (> 16 dB) up to 1.84 f 0, and the cross‐polarization level of 20 dB within 3‐dB beam range.